The Safety and Efficacy of Camrelizumab and Its Combination With Apatinib in Various Solid Cancers - Wang, Kunlun; Li, Bingxu; Li, Mengxi; Li, Shenglei; Yang, Hui; Yuan, Ling (Frontiers in Pharmacology, 2020)
Background: Camrelizumab (SHR1210) is a high-affinity, humanized immunoglobulin programmed cell death 1 (PD-1) monoclonal antibody. It was developed by Jiangsu Hengrui Medicine Co. Ltd and has been approved for relapsed or refractory classical Hodgkin lymphoma patients and hepatocellular carcinoma (HCC) patients in China. Apatinib is an orally administered vascular endothelial growth factor receptor-2 (VEGFR-2) tyrosine kinase inhibitor and has been approved for advanced gastric adenocarcinoma or gastroesophageal junction adenocarcinoma in China. Camrelizumab alone and its combination with apatnib have been used in the treatment of various solid cancers. Methods: We searched Embase, PubMed, and other databases with keyword “camrelizumab” or “SHR1210”, and evaluated the safety and efficacy data of the involved studies. Adverse events (AEs) mentioned in at least two studies were summarized, including any grade and grade ≥ 3 treatment-related AEs. Meanwhile, efficacy data were collected, such as overall response rate (ORR), disease control rate (DCR), duration of response (DoR), 6-month progression-free survival (PFS) rate, median PFS time, 12-month overall survival (OS) rate and median OS time. Results: The major AEs of camrelizumab alone were reactive cutaneous capillary endothelial proliferation (RCCEP), fatigue, aspartate aminotransferase (AST) increased, proteinuria, pruritus, and alanine transaminase (ALT) increased. The ORR and DCR were 20.2% (95% confidence interval (CI): 15.1%-26.6%, p=0.000, I2=70.360) and 45.8% (95% CI: 39.0%–52.7, p=0.256, I2=58.661), respectively. In the three studies of combination therapy, two studies were combined with apatinib and one combined with chemotherapy. For these studies, common AEs were hypertension, platelet count decreased, nausea, proteinuria, AST increased, and white blood cell count decreased. The pooled ORR, DCR and 6-month PFS rate were 41.8% (95% CI: 29.7%-54.9%, p=0.220, I2=86.265), 82.4% (95% CI: 75.9%-87.4%, p=0.000, I2=55.207), 56.2% (95% CI: 35.8%-74.6%, p=0.559, I2=79.739). Conclusion: Camrelizumab and its combination are tolerable and appears to be efficient in treating numerous solid cancers. The combination therapy appears to have better efficacy with durable toxicity. However, these remain to be shown in future studies. Besides, baseline lactate dehydrogenase (LDH), programmed cell death ligand 1 (PD-L1) expression, tumor mutation burden (TMB), and the incidence of RCCEP may be efficacy predictors and need to be clarified in further studies.